2007
DOI: 10.1109/iembs.2007.4352666
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experiments on the acceptability of animaloid companion robots by older people with early dementia

Abstract: Animaloid companion robots represent a very interesting paradigm. An increasing number of studies on this topic has been carried out in the past, involving such robots and older users affected by some kind of cognitive disease, from mild cognitive impairment (MCI) to more severe stages of Alzheimer's disease and other types of dementia. In the study described in this paper, an AIBO robotic dog was programmed and used to show simple reactive behaviors during the interaction with old adults. Experimental session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…While this disparity may result from individual variability, it is also possible robot design factors may be impairing wider acceptance. Similar differences have been observed for other devices; for example, research on AIBO has both shown good acceptability23 and found that it encouraged less interaction than a soft toy 24. Meanwhile, a review of acceptability towards robots used in aged care suggests a number of robots have failed 3…”
Section: Introductionmentioning
confidence: 54%
“…While this disparity may result from individual variability, it is also possible robot design factors may be impairing wider acceptance. Similar differences have been observed for other devices; for example, research on AIBO has both shown good acceptability23 and found that it encouraged less interaction than a soft toy 24. Meanwhile, a review of acceptability towards robots used in aged care suggests a number of robots have failed 3…”
Section: Introductionmentioning
confidence: 54%
“…Odetti et al (2007) performed a preliminary study examining the acceptability of animaloid companion robots (animalshaped robots that serve as substitute pets and can also be programmed to remind patients of daily activities such as taking pills or checking email) in patients with MCI and early dementia. Future studies are needed to determine whether these may also be beneficial for patients with late-life depression with comorbid cognitive impairment.…”
Section: Technological Interventionsmentioning
confidence: 99%
“…A social robot is an embodied system that can be perceived of as a social entity and that is capable of communicating with the user ( Broekens et al., 2009 ). While many social robots have been developed with older people and the disabled in mind ( Bogue, 2013 ), social robots may be useful and relevant for all members of society ( Dario et al., 2011 ; Prescott, 2017 ), with robots being developed for companionship ( Odetti et al., 2007 ) and assistance in public places working in areas such as retail, tourism, hospitality, and so on ( Hans et al., 2002 ; Harmo et al., 2005 ; Ivanov et al., 2017 ; Kachouie et al., 2014 ; Yamazaki et al., 2007 ). However, people are often wary of new technologies such as robots and Artificial Intelligence (AI); an unease that can be reinforced by public figures and media.…”
Section: Introductionmentioning
confidence: 99%